Targeting the gut microbiota: a new strategy for colorectal cancer treatment - Yue Hu; Peng Zhou; Kaili Deng; Yuping Zhou; Kefeng Hu (Journal of Translational Medicine, 2024)
Abstract Background How to reduce the high incidence rate and mortality of colorectal cancer (CRC) effectively is the focus of current research. Endoscopic treatment of early-stage CRC and colorectal adenomas (CAC) has a high success rate, but although several treatments are available for advanced CRC, such as surgery, radiotherapy, chemotherapy, and immunotherapy, the 5-year survival rate remains low. In view of the high incidence rate and mortality of CRC, early rational drug prevention for high-risk groups and exploration of alternative treatment modalities are particularly warranted. Summary Gut microbiota is the target of and interacts with probiotics, prebiotics, aspirin, metformin, and various Chinese herbal medicines (CHMs) for the prevention of CRC. In addition, the anti-cancer mechanisms of probiotics differ widely among bacterial strains, and both bacterial strains and their derivatives and metabolites have been found to have anti-cancer effects. Gut microbiota plays a significant role in early drug prevention of CRC and treatment of CRC in its middle and late stages, targeting gut microbiota may be a new strategy for colorectal cancer treatment.